EFFECTIVENESS OF PATIENT-CONTROLLED EPIDURAL ANALGESIA (PCEA) FOLLOWING CESAREAN SECTION AT BAI CHAY HOSPITAL IN 2025: A CASE SERIES OF 30 PATIENTS (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the analgesic efficacy of patient-controlled epidural analgesia (PCEA) after Cesarean section.Methods: A descriptive case series of 30 patients indicated for cesarean section who received patient-controlled epidural analgesia (PCEA) postoperatively at Bai Chay Hospital from March 2025 to October 2025.Results: The majority of patients were under 30 years of age (63.3%). The mean initial bolus volume was 5.93 ±0.83, mL (ranging from 4 to 7 mL). The mean pain intensity, measured by the Visual Analog Scale (VAS), decreased progressively over time: it was highest during the first 24 hours (mean VAS 4.8 ± 0.9, immediately postoperative) and declined to 1.5 ± 0.4, after 72 hours. All patients achieved satisfactory pain relief, with no cases requiring a transition to alternative analgesic modalities. Regarding dosage and consumption, the mean total local anesthetic dose over 72 hours was 287 ± 15 mg. Recorded side effects were mild and transient, primarily postoperative nausea and vomiting (PONV) at 26.7% and pruritus at 16.7%, none of which required specific medical intervention. There were no serious complications such as hypotension, urinary retention, respiratory depression, or post-dural puncture headache (PDPH).Conclusion: PCEA demonstrated good pain control in a group of 30 postpartum women monitored for 72 hours, with mild side effects.
Keywords: Epidural analgesia, Cesarean section, PCA pump.